Penyuluhan Pencegahan Penularan Covid-19 melalui Edukasi Social Distancing pada Anak Sekolah Dasar di Dusun Nyelak - M Deni siregar; Dukha Yunitasari; I Dewa Putu Partha (Lentera Negeri, 2020)
During this pandemic, the government appealed to social distancing as an effort to prevent the transmission of Covid-19. However, children actually do not understand what is happening and this understanding of social distancing is not fully understood by children because during childhood it is a play phase so that children activities and gather with their friends this will pose a risk of virus transmission. greater than. Therefore, during the Covid-19 pandemic, proper education is needed regarding the prevention of transmission of the virus to children. Providing children with an understanding of Covid-19 is very necessary so that children can prevent the transmission of the virus. Providing education to children about the corona virus or Covid-19 requires creativity and the delivery of information that is easily understood by children. Based on this, counseling activities on the prevention of covid-19 transmission were carried out through social distancing education for elementary school children in Nyelak Hamlet. This PKM aims to provide education and understanding to children and parents so that they can reduce gathering activities outside the home and avoid crowds while playing to prevent transmission of the virus. The content of this counseling is an understanding of the importance of effective social distance in preventing corona transmission, the reason for prohibiting social interaction with friends during the Covid-19 pandemic. With the implementation of this activity, it can provide understanding to children and parents so that they can avoid the transmission of Covid-19.